PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, KEBIJAKAN DIVIDEN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Siti Ratnasari; Muhammad Tahwin; Dian Anita Sari (BBM (Buletin Bisnis & Manajemen), 2018)
This study aims to prove and analyze the influence of investment decisions, funding decisions, dividend policies and profitability partially on the value of the company. This study also aims to provide consideration for investors in making investments. The research population includes manufacturing companies of consumer goods industry sector which is and still listed in Indonesia Stock Exchange period 2012-2014 of 36 companies. The sample was chosen by purposive sampling technique and obtained by 10 companies with observation value 30. Data were analyzed by using multiple linear regression analysis. Based on the result of data analysis, it is concluded that investment decision has positive effect not significant to value, funding decision has positive effect not significant to firm value, dividend policy has negative effect not significant to firm value, while profitability have positive significant effect to firm value. The value of determination coefficient (R2) of 0.927 indicates that investment decision variable, funding decision, dividend policy and profitability able to explain change of variable of company value equal to 92,7%, while the rest equal to 7,3% influenced by other variable outside research. Keywords: Company value, investment decision, funding decision, dividend policy and profitability.